Panniculitis is a common unrecognized histopathological feature of cutaneous leishmaniasis - Khalifa E Sharquie; Ammar F Hameed; Adil A Noaimi (Wolters Kluwer Medknow Publications, 2016)
Background: Cutaneous leishmaniasis (CL) is a parasitic cutaneous infection caused by Leishmania parasite. The histopathology is usually granulomatous in nature. Aims: The aim of the present study is to elucidate the histology of CL and evaluate the presence and the frequency of panniculitis among the affected patients. Settings and Design: Case series interventional study. Materials and Methods: Thirty-five patients with CL were diagnosed clinically between December-2012 and May-2013. Diagnostic confirmation established by smears, culture, and polymerase chain reaction (PCR). The histopathological assessment was carried out to study the general pathology and to look for the presence of panniculitis. Statistical Analysis Used: Simple statistics utilized via SPSS version 16.0 (SPSS, Inc., Chicago, USA). Results: Eighteen women and 17 men with CL were enrolled in the present work with a mean duration of their disease was 3 months. The results of the diagnostic tests were as follow: The smear was positive in 21 (60%) of cases, Leishman-Donovan (LD) bodies were seen in 7 (20%) patients, culture was positive in 24 (68%), and PCR was positive in 32 (91.4%) patients. The epidermal changes included acanthosis, pseudoepitheliomatous hyperplasia, ulceration, focal spongiosis, and interface dermatitis while the dermal changes were dependent on the spectrum of the disease, so in the ulcerative lesions there was lymphohistiocytic infiltration with foci of plasma cells and sometimes aggregate of LD bodies, whereas in the dry lesions the pathology is mainly of epithelioid granuloma. Panniculitis was seen in 16 (46%) cases as a diffuse lymphohistiocytic infiltration of both the septum and lobules of the subcutaneous layer of the skin. Conclusion: Panniculitis is an important feature of CL that must be differentiated from other diseases that can simulate CL such as chronic skin infections, Discoid lupus erythematosus, and cutaneous lymphoma.